Bibliometric analysis of publications on osteoarticular brucellosis - Semet, Cihan (The European Research Journal, 2024)
Objectives: The aim of this investigation was to undertake a thorough bibliometric analysis of publications between 1991 and 2022 to scrutinize and comprehend the research landscape of osteoarticular brucellosis, a zoonotic infection that affects bones and joints. Methods: We scrutinized the distribution of publications by various criteria, including country, institution, author, and journal. Furthermore, we executed citation analysis, established collaboration networks, and performed keyword co-occurrence analysis. Results: Our examination discovered 432 documents on this topic indexed in the Web of Science database, with a noticeable surge in publications over time. Turkey, the United States, and Iran were the leading nations in terms of research output. The University of Buenos Aires emerged as the most productive institution. The primary research areas were General Internal Medicine, Infectious Diseases, and Rheumatology. The primary beneficiary of this research was Agencia Nacional de Promoción Científica y Tecnológica (ANPCyT). Conclusions: This study furnishes valuable insights into worldwide research endeavors on osteoarticular brucellosis. These insights can steer future research directions, emphasizing the necessity for sustained collaboration and funding support to tackle this significant public health issue.